Molecular weight controlled sulfonated Poly(Arylene Ether)s and sulfonated Poly(Ether Ether ketone) polymer blends for fuel cell applications - KAYAMAN APOHAN, NİLHAN (My University, 2023)
We synthesized molecular weight-controlled and fluorine-containing PAEs (MWCPAEs) using decafluorobiphenyl (DFBP), 2-bis (4-hydroxyphenyl) propane (Bis A), and 2,2-Bis (4-hydroxyphenyl) hexafluoropropane (Bis AF). Later, commercially available PEEK and the MWCPAEs were sulfonated (SPEEK and SMWCPAE) and blended to fabricate blend membranes (BMs). All BMs have been prepared by solution casting method in 5 wt%-20 wt% concentrations using N,N-dimethylacetamide. The effects of chemical structures, sulfonation levels, MW and compositions on the membrane properties are discussed. We obtained miscible and mechanically compatible BMs. The highest proton conductivity (238.9 mS/cm) was determined for SPEEK70/S-DFBP-Bis-A based blend membrane (Mw: 48.355, 5wt. %). All chemical, mechanical, thermal, and hydrolytic properties of the BMs are comparable with, or better than, that of Nafion. We suggest that designing polymeric structures with desired MWs and sulfonation levels may enable enhanced properties and can help to design materials with on demand properties.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Fizik; Yoğun Madde 1:Yapısal, Mekanik ve Termal Özellikler; Temel Bilimler; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Physics; Condensed Matter 1: Structural, Mechanical and Thermal Properties; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; ENERJİ VE YAKITLAR; FİZİK, YOĞUN MADDE; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; PHYSICS; ENERGY & FUELS; PHYSICS, CONDENSED MATTER; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Fizik Bilimleri; Yakıt Teknolojisi; Yoğun Madde Fiziği; Enerji Mühendisliği ve Güç Teknolojisi; Renewable Energy, Sustainability and the Environment; Physical Sciences; Fuel Technology; Condensed Matter Physics; Energy Engineering and Power Technology; Blend membrane; Controlled-molecular weight; DMFC; PEMFC; poly(arylene ether)